2022
DOI: 10.3390/pharmaceutics14081530
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Pharmacometrics for Prediction of Pharmacokinetic Data: Differences, Similarities and Challenges Illustrated with Rifampicin

Abstract: Pharmacometrics (PM) and machine learning (ML) are both valuable for drug development to characterize pharmacokinetics (PK) and pharmacodynamics (PD). Pharmacokinetic/pharmacodynamic (PKPD) analysis using PM provides mechanistic insight into biological processes but is time- and labor-intensive. In contrast, ML models are much quicker trained, but offer less mechanistic insights. The opportunity of using ML predictions of drug PK as input for a PKPD model could strongly accelerate analysis efforts. Here exempl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 62 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…Bies et al demonstrated that the genetic algorithm (GA), as a combinatorial optimization approach, can efficiently develop a robust optimal model in an enormous search space. More recently, Keutzer et al 7 applied supervised ML algorithms, such as random forest (RF) and gradient boosting machine, in selecting the key features in the process of implementing a PK model of rifampicin. These applications have convincingly demonstrated the enormous potential of applying ML to nonlinear mixed-effect model selection.…”
Section: Pydarwin: a Machine Learning Enhanced Automated Nonlinear Mi...mentioning
confidence: 99%
“…Bies et al demonstrated that the genetic algorithm (GA), as a combinatorial optimization approach, can efficiently develop a robust optimal model in an enormous search space. More recently, Keutzer et al 7 applied supervised ML algorithms, such as random forest (RF) and gradient boosting machine, in selecting the key features in the process of implementing a PK model of rifampicin. These applications have convincingly demonstrated the enormous potential of applying ML to nonlinear mixed-effect model selection.…”
Section: Pydarwin: a Machine Learning Enhanced Automated Nonlinear Mi...mentioning
confidence: 99%
“…Clinically tested effects of galcanezumab dose (120mg and 240mg), validated through PK modeling, indicated a steady decrease in the concentration of free ligands resulting in the development of efficacious dose regimens. 160 A PK and target engagement (molecular interaction) study of anti-interferon-γ-induced protein 10 (IP-10) mAb was characterized, which concluded optimal dose strategy and scheduling of drug administration, i.e., approximately eight subcutaneously delivered dose intervals were required weekly in this case to reach steady state. 161 Specialized cell-based bioassays or potency assays, including ELISA, binding assays, competitive assays, cell signaling, ligand binding, proliferation, and proliferation suppression, are essential in ascertaining the mechanism of action and similarity with the parent molecule.…”
Section: Pharmacokinetics-pharmacodynamicsmentioning
confidence: 99%
“…Although still a relatively undeveloped area, experience with the application of ML/AI approaches for investigating doseexposure relationships is growing -an application of ML to predict rifampicin PK is a recent example [16] .…”
Section: Dose-exposure Relationships In Patientsmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) techniques are becoming more frequently applied to health care [14] , and their use in pharmacometrics is no exception [15] . Within the pharma-ceutical industry, they have been applied successfully to drug discovery, and there is an opportunity to utilize classical pharmacometric tools together with AI/ML in order to enhance drug development [16] .…”
Section: Introductionmentioning
confidence: 99%